Perceptions and use of evidence-based revision methods among undergraduate medical students - Ashfaq, Qurat-Ul-Ain; Ejaz, Taymmia; Baloch, Maria Hasan; Asghar Imam, Kamil (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess awareness, perceptions and use related to evidence-based revision methods by undergraduate medical students. Method: The descriptive cross-sectional study was conducted in three medical colleges of Rawalpindi-Islamabad, Pakistan, from December 01, 2019, to January 31, 2020, after approval from the ethics review committee of Army Medical College, Rawalpindi. The sample comprised undergraduate medical students of either gender. Data was collected online using a 10-item standardised questionnaire. Students were asked about the revision methods they used routinely and their perceptions of conventional and evidence-based revision methods. Data was analysed using SPSS 23. Results: Of the total 136 respondents, 92(67%) were females and 44(32.3%) were male students. The response from pre-clinical and clinical years was 67 (50.7%) and 69(49.2%), respectively. Highlighting was the most widely used revision method among students (70 students, 51%), followed by re-reading important points (65 students, 47.7%). 126 students (92%) had the opinion that conventional revision methods were effective learning tools. Only 52 students (38.2%) were aware of the term ‘evidence-based revision methods’. Digital tools based on principles of evidence-based revision were used by a minority of students which included use of online question banks by 21 students (15.4%), osmosis by 40 students (29.4%), sketchy pharma by 35 students (25%), flashcards by 19 (14%) and picmonic by only 3 (2.2%). More than 80% (114 students) responded that they wanted evidence-based revision methods to be incorporated into curriculum, and 85% (116 students) said they would like to have a workshop on these techniques. Conclusion: Most medical students were not aware of and were not using evidence-based revision methods, and relied on conventional revision tools. They were, however, eager to learn about newer revision strategies. Key Words: Medical education, Undergraduate, Learning strategies, Evidence-based revision methods, Active recall.